2000
DOI: 10.1152/jn.2000.84.3.1656
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of Human Brain in Olfactory Processing: A PET Study

Abstract: This study describes the functional anatomy of olfactory and visual naming and matching in humans, using positron emission tomography (PET). One baseline control task without olfactory or visual stimulation, one control task with simple olfactory and visual stimulation without cognition, one set of olfactory and visual naming tasks, and one set of olfactory and visual matching tasks were administered to eight normal volunteers. In the olfactory naming task (ON), odors from familiar items, associated with some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 72 publications
7
71
0
Order By: Relevance
“…The authors suggested that the participants used a strategy involving mental imagery to achieve the task. In a PET study of the cognitive component of olfactory processing, left cuneus was activated when participants named the odors (Qureshy et al, 2000). The authors suggest that the task involved some imagery to ascertain the name of the odor and indicated that the visual cortex is involved in mental imagery tasks (see also Kosslyn, 1988;Royet et al, 1999).…”
Section: Activation Of Posterior Regionsmentioning
confidence: 99%
“…The authors suggested that the participants used a strategy involving mental imagery to achieve the task. In a PET study of the cognitive component of olfactory processing, left cuneus was activated when participants named the odors (Qureshy et al, 2000). The authors suggest that the task involved some imagery to ascertain the name of the odor and indicated that the visual cortex is involved in mental imagery tasks (see also Kosslyn, 1988;Royet et al, 1999).…”
Section: Activation Of Posterior Regionsmentioning
confidence: 99%
“…Analogously, neuroimaging studies have reported activation of visual cortical areas during the performance of various purely olfactory tasks (Royet et al, 1999;Qureshy et al, 2000;Zatorre et al, 2000;Dade et al, 2002). One possible explanation for these visual-olfactory interactions is that subjects decide upon the identity of the stimulus, based entirely on processing within olfactory brain regions, after which they visualize the corresponding object.…”
Section: Introductionmentioning
confidence: 97%
“…Although the cerebellum is not traditionally considered part of the olfactory system, cerebellar activity has been consistently observed in functional imaging studies of olfaction (Small et al, 1997;Yousem et al, 1997;Sobel et al, 1998;Qureshy et al, 2000;Savic et al, 2000;Zatorre et al, 2000;Cerf-Ducastel and Murphy, 2001;Ferdon and Murphy, 2003). Despite this, the pathways through which olfactory information reaches the cerebellum and the functional role of the cerebellum in olfaction remain unknown.…”
Section: Introductionmentioning
confidence: 99%